Nitric oxide (NO) - a wide-range modulator of life’s processes.The role in pathomechanism of alcohol addiction and withdrawal symptoms - Pedrycz, Agnieszka; Ciechan, Alicja; Siermontowski, Piotr; Polz, Dorota (Current Problems of Psychiatry, 2011)
Introduction and aim: The aim of this study was to analyze the available literature in terms of understanding the functions and mechanisms of endo-and exogenous nitric oxide (NO). Particular attention was paid to the in-volvement of nitric oxide donors in the pathogenesis of alcohol dependence and withdrawal syndrome.Results and discussion: Nitric oxide was discovered in 1770. Numerous studies about NO biochemistry have been carried out since that time In 1998 Robert F. Furchgott, Luis Ignarro and Ferid Murad received the Nobel Prize in medicine for their research on the sequence of metabolic changes: L-arginine → NO. There are various mechanisms leading to the activation of individual NOS isoforms and thus to NO synthesis. Moreover, NO formed in the reaction catalyzed by different NOS, has various functions. Excessive endogenous NO is involved in the pathogenesis of many diseases, e.g. atherosclerosis, degenerative diseases of the nervous system, inflammations, autoimmune diseases and cancers. Deficient endogenous NO is implicated in the development of hypertension, preeclampsia, arteriosclerosis, hypercholesterolemia. Exogenous NO is administered to patients with venous atheros-clerosis of the lower limbs, coronary disease and pregnancy-induced hypertension. An increase or a slight decrease in NO metabolites plasma concentration following 4-week abstinence may be a predictor of alcohol drinking relapse during the next five months.